Pengaruh Kombinasi Pupuk Kandang Ayam dan Pupuk NPK terhadap Pertumbuhan dan Hasil Tanaman Terong (Solanum melongena L.) - Ariyanti, Oktavia Dwi; aini, nurul (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2024)
Eggplant (Solanum melongena L.) is a type of fruit vegetable that is liked by many people and has an ever-increasing demand. Productivity needs to be increased starting from technical improvements in eggplant cultivation to post-harvest treatment. One of the things that need to be considered in cultivating is the availability of sufficient nutrients to support the growth and yield of eggplant plants. The addition of nutrients can be done by fertilizing. The fertilizers given consist of two types, namely organic fertilizers and inorganic fertilizers. This study aims to study and analyze the effect of the right dose of a combination of NPK fertilizer and chicken manure on the growth and yield of eggplant plants. This research was carried out from November 2020 to February 2021 in Situbondo City. This study used a randomized block design (RBD) with 10 treatments and was repeated 3 times. The dose of chicken fertilizer consisted of 5, 10 and 15 tons ha-1, the dose of NPK fertilizer consisted of 200, 300 and 400 kg ha-1. The results showed that the addition of chicken manure and NPK fertilizer had a significant effect on eggplant growth and yield. The treatment of 300 kg ha-1 NPK + 5 tons ha-1 chicken manure had a significant effect on plant height and fruit weight per plant, while 200 kg ha-1 NPK + 15 tons ha-1 chicken manure had a significant effect on the number of leaves, area leaves, number of flowers, fruit length, and fruit diameter.